Self-approximation of periodic Hurwitz zeta-functions - Karikovas, Erikas (Nonlinear Analysis: Modelling and Control, 2015)
Let ζ(s,ω;A) be the periodic Hurwitz zeta-function. We look for real numbers α and β for which there exist "many" real numbers τ such that the shifts ζ(s+iατ,ω;A) and ζ(s+iβτ,ω;A) are "near" each other.
Keywords: self-approximation; periodic Hurwitz zeta-functions